The Reality of Utilizing Modern Educational Technology and the Difficulties Faced in Kindergartens - a Case Study on a Sample of Kindergartens in Lattakia City - - Ali, Khodor; Sbeira, Fouad (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study shed light at the reality of utilizing modern educational technology in kindergartens in Lattakia. It also aims at highlighting the difficulties faced in the process of utilizing such technology. A review of the literature about the topic has been done. Data have been collected through interviews with some kindergarten teachers and through a questionnaire distributed on a random sample consisting of 48 teachers. The study reveals the following findings: 1. The kindergarten teachers are aware of the importance of utilizing modern educational technology on ongoing basis. 2. There are no training courses for teachers on how to design educational materials related to such technology and develop them. This made it difficult for these teachers to utilize technology in the teaching/learning process. this difficulty has been mentioned as the biggest one facing the teachers. 3. Depending on the variables of the years of teaching experience and type of kindergarten, there appear no significant statistical differences with respect to the view of kindergarten teachers about the importance of utilizing modern technology in the teaching/learning process and the difficulty of such utilization. The study suggests conducting training courses for teachers to train them on the skills of utilizing modern educational technology and designing specific pedagogical materials that help in conveying information smoothly. The study suggests too that these training courses could be very useful in encouraging the teachers to utilize modern educational technology in an effective and systematic way in their lessons.